Role of Mus musculus in the transmission of several pathogens in poultry farms - Manabella Salcedo, Iris Belen (2021)
This study aimed to analyze the role of Mus musculus as a host of Leptospira spp., lymphocytic choriomeningitis virus (LCMV) and Toxoplasma gondii, in poultry farms of Buenos Aires province, Argentina, and to assess the potential risk of transmission to humans and domestic or breeding animals. Samplings were performed between 2009 and 2011 (S1) and during 2016 (S2). In S1, we studied the prevalence of infection for Leptospira spp. and LCMV, whereas, in S2, we studied the prevalence of infection for Leptospira spp. and T. gondii. In S1, we found an overall Leptospira spp. prevalence in M. musculus of 18% (14/79) and no positive serum samples for LCMV (0/166). In S2, we detected no positive individuals for Leptospira spp. (0/56) and an overall T. gondii seroprevalence of 3.6% (2/56). The probability of Leptospira spp. infection in M. musculus was higher in reproductively active individuals and in samplings subsequent to months with high accumulated precipitation. Our results suggest that, in the poultry farms studied, the presence of M. musculus may be a risk factor in the transmission of Leptospira spp. and T. gondii to humans and domestic animals. The management of farms should include biosecurity measures for farm workers and more effective rodent control.